The impact of advanced diabetes technologies on safety and glycemic control during exercise in individuals with type 1 diabetes - Więckowska, Katarzyna; Bruska, Natalia; Cemaga, Roman; Patalong, Mikołaj; Błaszkowski, Bartłomiej; Czapliński, Mieszko; Kołodziej, Przemysław; Król, Maria; Hebda, Patryk; Bylik, Andrzej (Quality in Sport, 2026)
Background: Type 1 diabetes (T1D) represents an increasing epidemiological challenge worldwide. In Europe, the fastest rise in T1D incidence is currently observed in the northern and central regions. Effective glycemic control remains crucial for preventing acute and chronic complications, particularly in physically active individuals. Aim: This study aims to evaluate the impact of modern technologies supporting intensive insulin therapy on glycemic regulation, with a special focus on their role during physical activity. Material and Methods: A comprehensive literature review was conducted analyzing the use of continuous glucose monitoring (CGM) systems and continuous subcutaneous insulin infusion (CSII) via personal insulin pumps. Emphasis was placed on their effects on metabolic control and the reduction of severe hypoglycemia risk compared to conventional treatment. The function of advanced hybrid closed-loop (AHCL) systems, such as the MiniMed 780G, was also examined in relation to exercise-induced glycemic fluctuations. Results: CGM systems enable predictive monitoring of glycemic trends, shortening the response time to imminent hypoglycemia by approximately 20 minutes during physical activity. The application of AHCL systems provides automated protection against intra- and post-exercise hypoglycemia through features such as the SmartGuard algorithm and temporary target adjustments. These technologies significantly improve metabolic stability, even under conditions of intensive training. Conclusion: The integration of advanced diabetes management technologies with regular physical activity offers a new standard in T1D care. This approach facilitates enhanced glycemic control and hypoglycemia prevention, supporting safer and more effective engagement in physical exercise.